Konflikt, fellesskap og forandring Foreldreskap og sosial kontroll i innvandrede familier fra Pakistan, Somalia og Sri Lanka - Friberg, Jon Horgen (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2019)
"In recent years, organizations and authorities in Norway have put a critical spotlight on parenting practices among non-Western immigrants, based on a concern for young people's autonomy and self-determination. The purpose of this book - which deals with parenting and social control in immigrant families from Pakistan, Somalia and Sri Lanka - is to shed light on on this collision between different family norms and practices from different perspectives, and thus help to understand why family relations and social control have become a topic of contention in today's multicultural Norway. The books starting point is a sociological perspective on cultural differences, social control and change in a migration context. A key point of focus in the empirical analyzes are parental restrictions in young people's social life. How common are such restrictions within different groups? What significance do factors such as religiosity and socio-economic resources play in the exercise of social control? And what are the consequences for children's social participation, mental health and well-being? One aim is to contribute systematic quantitative knowledge on such issues. At the same time, the book contributes to a more qualitative understanding of people's experiences and actions. How do parents from countries like Pakistan, Somalia and Sri Lanka experience raising children and young people in Norway? What concerns have they had regarding their children's encounters with various parts of Norwegian society? And how do young people navigate between different expectations and demands from the families and communities on the one hand and among their peers and the larger society on the other? We focus on the question of social change. Is the organization of family relationships and the exercise of social control within immigrant populations characterized by continuity or change? And what kind of mechanisms drive such changes forward? The book, which is published as part of the Children of Immigrants Longitudinal Study in Norway, will illuminate these questions using quantitative data from a comprehensive survey of 16-17 year olds in Oslo and Akershus, as well as qualitative interviews - individually and in groups - with parents, adolescents and young adults with immigrant backgrounds as well as people in public help services and NGOs. "